Analyzing the Relationship Between Child-to-Parent Violence and Perceived Parental Warmth - Cano-Lozano, M. Carmen; Rodríguez-Díaz, F. Javier; León, Samuel P.; Contreras, Lourdes (Frontiers in Psychology, 2020)
The relationship between child-to-parent violence (CPV) and the perceived parental warmth dimension has been well established. However, it is necessary to further investigate the nature of this relationship considering the involvement of other variables. The objective of this study was to analyze the role of cognitive (hostile attribution), emotional (anger), and social variables (deviant peer group and drug use) in the relationship between the perceived parental warmth dimension (warmth-communication and criticism-rejection) and CPV motivated by reactive or instrumental reasons. The sample consisted of 1,599 Spanish adolescents (54.8% girls) between the ages of 12 and 18 years (Mage = 14.6, SD = 1.6 years). The results indicate that perceived parental warmth is negatively correlated with hostile attribution, adolescent anger, relationship with a deviant peer group, while perceived parental criticism is positively linked to these variables. Likewise, hostile attribution and adolescent anger are positively linked to reactive CPV. Relationship with a deviant peer group is associated with drug use, which also predicts both reactive and instrumental CPV. In sum, a lack of perceived parental warmth has important repercussions in the form of the psychological and social maladjustment of children, which in turn is differentially correlated with reactive or instrumental CPV. Thus, prevention and intervention programs for CPV should consider, on the one hand, working with parents on parental practices that incorporate parental warmth as a fundamental element and, on the other hand, working with children on cognitive, emotional, and social aspects, taking into account the different motivations for this type of violence.